2021
DOI: 10.1002/ar.24745
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of acupuncture on the sleep structure of patients with insomnia: A systematic review and meta‐analysis

Abstract: This study aims to evaluate the efficacy of acupuncture on the sleep structure of patients with insomnia, so as to provide a valuable basis for the effectiveness of acupuncture in the treatment of insomnia. We conducted searches based on MeSH terms and free words in Cochrane Library, PubMed, Web of science, CKNI (China Knowledge Resource Integrated Database), WanFang Database, and Chongqing VIP Information from the inception of these database until 10 July 2020 for randomized controlled trials (RCTs) that inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Five systematic reviews and meta‐analyses and three network meta‐analyses investigated the efficacy of acupuncture on sleep outcomes. In summary, six of them found significant reductions in the Pittsburgh Sleep Quality Index (PSQI) total score (Cao et al, 2019; Fang et al, 2021; Kwon et al, 2021; Liu et al, 2020; Lu et al, 2022; Zhang et al, 2020), two reviews found significant decreases in the Insomnia Severity Index (ISI) (Liu et al, 2020; Zhang et al, 2020), and one study found reduced subjective sleep onset latency (SOL) (Cao et al, 2019). With respect to objective sleep parameters, results were mixed: three reviews reported significant effects (Fang et al, 2021; Zhang et al, 2020; Zhao et al, 2021), while two reviews found no significant effects (Jiang et al, 2019; Liu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five systematic reviews and meta‐analyses and three network meta‐analyses investigated the efficacy of acupuncture on sleep outcomes. In summary, six of them found significant reductions in the Pittsburgh Sleep Quality Index (PSQI) total score (Cao et al, 2019; Fang et al, 2021; Kwon et al, 2021; Liu et al, 2020; Lu et al, 2022; Zhang et al, 2020), two reviews found significant decreases in the Insomnia Severity Index (ISI) (Liu et al, 2020; Zhang et al, 2020), and one study found reduced subjective sleep onset latency (SOL) (Cao et al, 2019). With respect to objective sleep parameters, results were mixed: three reviews reported significant effects (Fang et al, 2021; Zhang et al, 2020; Zhao et al, 2021), while two reviews found no significant effects (Jiang et al, 2019; Liu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to objective sleep parameters, results were mixed: three reviews reported significant effects (Fang et al, 2021;Zhang et al, 2020;Zhao et al, 2021), while two reviews found no significant effects (Jiang et al, 2019;Liu et al, 2020). Cao et al (2019) conducted a meta-analysis and reported significant reductions in the PSQI total score and subjective SOL compared to sham acupuncture/no treatment.…”
Section: Acupuncturementioning
confidence: 99%
See 2 more Smart Citations
“…Electro-acupuncture is a characteristic traditional Chinese non-pharmacological method. It not only can improve sleep architecture ( 14 ) and prolong deep sleep time in patients with insomnia ( 15 ) but also can improve motor symptoms in patients with movement disorders ( 16 ). Polysomnography (PSG) is considered the gold standard for the diagnosis of non-rapid eye movement (NREM) parasomnias ( 17 ), particularly valuable for individuals with complex medical histories.…”
Section: Discussionmentioning
confidence: 99%